Curcumin generates oxidative stress and induces apoptosis in adult schistosoma mansoni worms - De Aguiar, Daniela Paula (2018)
Inducing apoptosis is an interesting therapeutic approach to develop drugs that act against helminthic parasites. Researchers have investigated how curcumin (CUR), a biologically active compound extracted from rhizomes of Curcuma longa, affects Schistosoma mansoni and several cancer cell lines. This study evaluates how CUR influences the induction of apoptosis and oxidative stress in couples of adult S. mansoni worms. CUR decreased the viability of adult worms and killed them. The tegument of the parasite suffered morphological changes, the mitochondria underwent alterations, and chromatin condensed. Different apoptotic parameters were determined in an attempt to understand how CUR affected adult S. mansoni worms. CUR induced DNA damage and fragmentation and increased the expression of SmCASP3/7 transcripts and the activity of Caspase 3 in female and male worms. However, CUR did not intensify the activity of Caspase 8 in female or male worms. Evaluation of the superoxide anion and different antioxidant enzymes helped to explore the mechanism of parasite death further. The level of superoxide anion and the activity of Superoxide Dismutase (SOD) increased, whereas the activity of Glutathione-S-Transferase (GST), Glutathione reductase (GR), and Glutathione peroxidase (GPX) decreased, which culminated in the oxidation of proteins in adult female and male worms incubated with CUR. In conclusion, CUR generated oxidative stress followed by apoptotic-like-events in both adult female and male S. mansoni worms, ultimately killing them.